2018
DOI: 10.1159/000492280
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis of Differentially Expressed Profiles of Circular RNAs in a Mouse Model of Intestinal Ischemia/Reperfusion Injury with and Without Ischemic Postconditioning

Abstract: Background/Aims: Ischemic postconditioning (iPoC) represents a promising strategy to mitigate ischemia/reperfusion (I/R) injury of the intestine, yet the mechanisms of this treatment remain to be elucidated. Circular RNAs (circRNAs), a novel class of endogenous non-coding RNAs, have recently been recognized as important regulators of gene expression and pathological processes. Here, we aimed to investigate the expression patterns of circRNAs after intestinal I/R with and without iPoC and, furthermore, to explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 55 publications
(54 reference statements)
0
11
0
Order By: Relevance
“…Specifically, profiling analysis of circRNAs and mRNAs in human temporal lobe epilepsy with hippocampal sclerosis has been conducted [ 44 ]. Furthermore, microarray and functional enrichment analysis of circRNAs and mRNAs in a mouse model of intestinal IR injury with and without ischemic post-conditioning was performed [ 58 ]. Here, our results may indicate the specificity of the formation and degradation of circRNAs and mRNAs during cerebral IR, as well as the specific mechanisms of functioning of various linear and circular RNAs, which appear to be related to the uniqueness of their structures.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, profiling analysis of circRNAs and mRNAs in human temporal lobe epilepsy with hippocampal sclerosis has been conducted [ 44 ]. Furthermore, microarray and functional enrichment analysis of circRNAs and mRNAs in a mouse model of intestinal IR injury with and without ischemic post-conditioning was performed [ 58 ]. Here, our results may indicate the specificity of the formation and degradation of circRNAs and mRNAs during cerebral IR, as well as the specific mechanisms of functioning of various linear and circular RNAs, which appear to be related to the uniqueness of their structures.…”
Section: Discussionmentioning
confidence: 99%
“…In our literature search, 15 studies made use of transcriptomics technology to study intestinal IR injury versus sham surgery in animals [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] (Table 1, part I). The aims of these studies ranged from exploring overall changes in gene expression in intestinal IR for a better understanding of the pathological process and/or to identify potential therapeutic targets [10,16,17,21], to specific testing of a therapeutic intervention [11,13,15,18,19], or both [12,14,23,24]. For these studies, mice were most commonly used to establish an intestinal IR model [11,13,[15][16][17][18][19]21], and two studies made use of rats [10,14].…”
Section: Transcriptomicsmentioning
confidence: 99%
“…The aims of these studies ranged from exploring overall changes in gene expression in intestinal IR for a better understanding of the pathological process and/or to identify potential therapeutic targets [10,16,17,21], to specific testing of a therapeutic intervention [11,13,15,18,19], or both [12,14,23,24]. For these studies, mice were most commonly used to establish an intestinal IR model [11,13,[15][16][17][18][19]21], and two studies made use of rats [10,14].…”
Section: Transcriptomicsmentioning
confidence: 99%
“…(reported identified exonuclease-treated transcripts >25 000) [ 3 , 4 ] and Salzman et al (identified circRNA from different human cell types) [ 5 ] showed the abundance of circRNAs and established it as emerging class of noncoding RNAs. Till now, circ are identified in a number of organisms including model organisms like humans [ 3 , 6–9 ], worms [ 10 ], Drosophila [ 10 , 11 ], mouse [ 12–14 ], chicken [ 15 , 16 ], and pig [ 17–19 ]. Circs are known to exist as cell-line specific and tissue-specific isoforms [ 20 , 21 ] and are also known to have conserved splice sites.…”
Section: Introductionmentioning
confidence: 99%